Evaluation of accessible mineral surface areas for improved prediction of mineral reaction rates in porous media. (15th May 2017) - Beckingham, Lauren E.; Steefel, Carl I.; Swift, Alexander M.; Voltolini, Marco; Yang, Li; Anovitz, Lawrence M.; Sheets, Julia M.; Cole, David R.; Kneafsey, Timothy J.; Mitnick, Elizabeth H.; Zhang, Shuo; Landrot, Gautier; et al.
Abstract: The rates of mineral dissolution reactions in porous media are difficult to predict, in part because of a lack of understanding of mineral reactive surface area in natural porous media. Common estimates of mineral reactive surface area used in reactive transport models for porous media are typically ad hoc and often based on average grain size, increased to account for surface roughness or decreased by several orders of magnitude to account for reduced surface reactivity of field as opposed to laboratory samples. In this study, accessible mineral surface areas are determined for a sample from the reservoir formation at the Nagaoka pilot CO2 injection site (Japan) using a multi-scale image analysis based on synchrotron X-ray microCT, SEM QEMSCAN, XRD, SANS, and FIB-SEM. This analysis not only accounts for accessibility of mineral surfaces to macro-pores, but also accessibility through connected micro-pores in smectite, the most abundant clay mineral in this sample. While the imaging analysis reveals that most of the micro- and macro-pores are well connected, some pore regions are unconnected and thus inaccessible to fluid flow and diffusion. To evaluate whether mineral accessible surface area accurately reflects reactive surface area a flow-through core experiment is performed and modeled at the continuum scale. The core experiment is performed under conditions replicating the pilot site and the evolution of effluent solutes in the aqueous phase is tracked. Various reactive surface area models are evaluated for their ability to capture the observed effluent chemistry, beginning with parameter values determined as a best fit to a disaggregated sediment experiment (Beckingham et al., 2016) described previously. Simulations that assume that all mineral surfaces are accessible (as in the disaggregated sediment experiment) over-predict the observed mineral reaction rates, suggesting that a reduction of RSA by a factor of 10–20 is required to match the core flood experimental data. While the fit of the effluent chemistry (and inferred mineral dissolution rates) greatly improve when the pore-accessible mineral surface areas are used, it was also necessary to include highly reactive glass phases to match the experimental observations, in agreement with conclusions from the disaggregated sediment experiment. It is hypothesized here that the 10–20 reduction in reactive surface areas based on the limited pore accessibility of reactive phases in core flood experiment may be reasonable for poorly sorted and cemented sediments like those at the Nagaoka site, although this reflects pore rather than larger scale heterogeneity.